Admittances characteristics by sepsis in the Spanish internal medicine services between 2005 and 2015: mortality pattern. Issue 3 (2nd April 2020) - Canora, Jesús; Moreno, Guillermo; Marco, Javier; San Román, Jesús; Plaza, Susana; Zapatero, Antonio; Barba, Raquel
ABSTRACT: Background: Studies in recent years suggest an increase in the incidence of sepsis but a decrease in mortality. The aim of this study is to describe the characteristics of patients discharged after a sepsis episode from Spanish internal medicine services between 2005 and 2015. Results: Since 2005, in which there were a total of 4, 319 cases, sepsis hospitalizations has been consistently increasing yearly reaching a total of 25, 820 cases in 2015. We observed that septic patients are older and with higher comorbidity than the general population admitted in Internal Medicine. On the other hand, we found a decreasing trend in the mortality rates of patients with sepsis in our series going from 35.7% in 2005 to 30.1% in 2015 (p < 0.005). Discussion: In our study, a higher comorbidity at admission and developing complications during admittance, conditioned a higher probability of death due to sepsis. The variables that were associated with increased mortality risk were age, acute renal failure, acute respiratory failure, lactic acidosis, septic shock and chronic heart failure. Conclusion: As in other similar studies, we observed an increase in the hospitalizations by sepsis as a diagnosis at discharge during the study period in Internal Medicine services with a simultaneous decrease in mortality. Comorbidity at admission and complications during admittance condition mortality.